Dysregulated apoptosis and NFκB expression in COPD subjects - Brown, Vanessa; Elborn, J Stuart; Bradley, Judy; Ennis, Madeleine (Respiratory research, 2009)
BACKGROUND: The abnormal regulation of neutrophil apoptosis may contribute to the ineffective resolution of inflammation in chronic lung diseases. Multiple signalling pathways are implicated in regulating granulocyte apoptosis, in particular, NFκB (nuclear factor-kappa B) signalling which delays constitutive neutrophil apoptosis. Although some studies have suggested a dysregulation in the apoptosis of airway cells in chronic obstructive pulmonary disease (COPD), no studies to date have directly investigated if NFκB is associated with apoptosis of airway neutrophils from COPD patients. The objectives of this study were to examine spontaneous neutrophil apoptosis in stable COPD subjects (n = 13), healthy smoking controls (n = 9) and non-smoking controls (n = 9) and to investigate whether the neutrophil apoptotic process in inflammatory conditions is associated with NFκB activation. METHODS: Analysis of apoptosis in induced sputum was carried out by 3 methods; light microscopy, Annexin V/Propidium iodide and the terminal transferase-mediated dUTP nick end-labeling (TUNEL) method. Activation of NFκB was assessed using a flow cytometric method and the phosphorylation state of IκBα was carried out using the Bio-Rad Bio-Plex phosphoprotein IκBα assay. RESULTS: Flow cytometric analysis showed a significant reduction in the percentage of sputum neutrophils undergoing spontaneous apoptosis in healthy smokers and subjects with COPD compared to non-smokers (p < 0.001). Similar findings were demonstrated using the Tunel assay and in the morphological identification of apoptotic neutrophils. A significant increase was observed in the expression of both the p50 (p = 0.006) and p65 (p = 0.006) subunits of NFκB in neutrophils from COPD subjects compared to non-smokers. CONCLUSION: These results demonstrate that apoptosis is reduced in the sputum of COPD subjects and in healthy control smokers and may be regulated by an associated activation of NFκB.